Is Healthy Neuroticism Associated with Health Behaviors? A Coordinated Integrative Data Analysis - Eileen K. Graham; Sara J. Weston; Nicholas A. Turiano; Damaris Aschwanden; Tom Booth; Fleur Harrison; Bryan D. James; Nathan A. Lewis; Steven R. Makkar; Swantje Mueller; Kristi M. Wisniewski; Tomiko Yoneda; et al. (Collabra: Psychology, 2020)
Current literature suggests that neuroticism is positively associated with maladaptive life choices, likelihood of disease, and mortality. However, recent research has identified circumstances under which neuroticism is associated with positive outcomes. The current project examined whether “healthy neuroticism”, defined as the interaction of neuroticism and conscientiousness, was associated with the following health behaviors: smoking, alcohol consumption, and physical activity. Using a pre-registered multi-study coordinated integrative data analysis (IDA) approach, we investigated whether “healthy neuroticism” predicted the odds of engaging in each of the aforementioned activities. Each study estimated identical models, using the same covariates and data transformations, enabling optimal comparability of results. These results were then meta-analyzed in order to estimate an average (N-weighted) effect and to ascertain the extent of heterogeneity in the effects. Overall, these results suggest that neuroticism alone was not related to health behaviors, while individuals higher in conscientiousness were less likely to be smokers or drinkers, and more likely to engage in physical activity. In terms of the healthy neuroticism interaction of neuroticism and conscientiousness, significant interactions for smoking and physical activity suggest that the association between neuroticism and health behaviors was smaller among those high in conscientiousness. These findings lend credence to the idea that healthy neuroticism may be linked to certain health behaviors and that these effects are generalizable across several heterogeneous samples.
Keywords: 300; Healthy Neuroticism; Health Behaviors; Big Five; IALSA; Coordinated IDA